Marker-assisted introgression of resistance to cassava mosaic disease into Latin American germplasm for the genetic improvement of cassava in Africa - Okogbenin, Emmanuel; Porto, M.C.M.; Egesi, Chiedozie N.; Mba, C; Espinosa, E.; Santos Meléndez, Luís Guillermo; Ospina, C.; Marín, J.A.; Barrera Sabogal, E.; Gutiérrez Artunduaga, Janneth Patricia; Ekanayake, I.J.; Iglesias, C.A.; et al. (Wiley, 2007)
The gene pools for breeding cassava (Manihot esculenta Crantz) in Africa currently contain only a fraction of the existing genetic variation found in Latin America where the crop originates. Our research aimed to broaden the genetic base in Africa by introducing Latin American (LA) germplasm. The first set of introductions comprised sexual seeds that led to the evaluation of 20,032 seedlings in Nigeria between 1990 and 1994. A second set comprised in vitro cultures, where the dominant CMD2 gene for cassava mosaic disease (CMD) resistance was introgressed into LA germplasm through marker-assisted selection (MAS). Through MAS 156 genotypes were preselected for the gene and evaluated in Nigeria between 2004 and 2006. Initial results from the first set of introductions indicated that LA germplasm was highly susceptible to CMD, minimizing its usefulness in African cassava-breeding programs. In the second set of introductions from LA, introgression of the CMD2 gene resulted in high CMD resistance under African field conditions. Now at advanced stages in the African breeding program, 14 genotypes combining CMD resistance and high yield are being evaluated. Marker-assisted introgression of CMD resistance into LA germplasm has improved the potential value of LA germplasm for Africa and enhanced the prospect of elite LA genotypes being released as improved varieties in Africa.